Web-Based Complaints Service Information System at Dewantara District Office - Amrina Amrina; Aslam Aslam; Khoirul Islam; I Ketut Sutapa; Kurniawansyah Kurniawansyah; Dahlan Abdullah; Zalfie Ardian (International Journal of Engineering, Science and Information Technology, 2024)
The Complaint Service Information System is a web-based platform designed for the Dewantara District Office. The title Complaint Service Information System is based on the need for technological solutions to improve the quality of public services, especially in handling public complaints. This system was chosen because it facilitates more efficient complaint reporting, increases transparency, and speeds up responses to issues raised by the public. By applying information technology in handling complaints, it is hoped that we can create a public service environment that is more responsive, open and adaptive to the ever-growing needs of society. The process of creating a complaint service information system involves several main stages. First, the needs analysis stage is carried out to identify and understand the needs of users and related parties in handling complaints. This involves a survey and analysis of associated documents. Next, the system design and design stage involves database structure, user interface, and business logic. This Information System design process involves critical steps to ensure the success and effectiveness of the system, including coding, creating a user interface, and setting up a database. The results of designing the Complaint Service Information System include a simple and responsive user interface, an online complaint form, a status tracking system, and analytical reports. A structured and secure database stores, manages, and retrieves complaint data. Afterwards, the implementation phase involves running the entire system and, if necessary, data migration. Through the creation of this Information System, it is hoped to evaluate the impact of the level of accessibility and ease of navigation in the system on employee performance in searching, monitoring and managing incoming complaints. With a web-based approach, this system provides easy, fast access for users from various locations and increases transparency in managing services provided to the community.